A introdução da inteligência artificial no Poder Judiciário sob a perspectiva do acesso à justiça pela via dos direitos - Wilson de Freitas Monteiro (2023)
This dissertation aimed to problematize and investigate the application of artificial intelligence (AI) mechanisms in the Judiciary, from the perspective of access to justice, essentially through the way of the rights. The research work carried out examined the integration processes of mechanisms incorporated by data and computational algorithms in the judicial sector and its application in courts across the country. It was argued that machine learning, if applied to the Judiciary, considering the risks of its implementation, tends to exponentiate a strong instrument for matching the three dimensions of access to justice through the way of the rights, as elaborated by Avritzer, Marona and Gomes (2014), namely: (I) equal access to the judicial system; II) guarantee of the effectiveness of the rights, through information about these rights, making it possible to understand what rights the subject has and identify what mechanisms the justice system has to offer him; and (III) the possibility of participating in shaping the law itself, based on the identification of new categories of law. Throughout the work, it was found that AI models, when not properly structured, can stigmatize individuals into categories and drive alienation of entire groups, preventing access to rights and opportunities, as clarified by O'Neil (2020), while that, as stated by Rodrigues (2021), if restricted to functions of an operational and instrumental nature, the use of the mechanisms in question is fertile and deserves to be expanded.